Electrical Circuit Model of Fractional Flow Reserve in Cerebrovascular Disorders - Pranevicius, H.; Naujokaitis, D.; Pilkauskas, V.; Pranevicius, O.; Pranevicius, M. (Elektronika ir Elektrotechnika, 2014)
We developed electrical circuit based model for the different components of the cerebral circulation, what allowed us to simulate cerebral blood flow in a variety of cerebrovascular disorders. This approach allowed us to derive a set of equations by which relative maximum, or fractional flow reserve, can be defined and calculated in three relevant sites: the stenotic artery, in the veins related to the stenotic artery, and in the collateral circulation of the affected region of the brain. Our results create theoretical basis for the entirely new approach to cerebrovascular disorders that currently emphasise anatomical identification of the disease to guide the treatment, such as the degree of arterial luminal stenosis obtained from various imaging modalities. In doing so, we directly address an urgent need for stroke experts to advance the care of their patients, since current approach of stroke treatment has not been meaningfully successful. DOI: http://dx.doi.org/10.5755/j01.eee.20.10.8877